(untitled) (Baghdad Science Journal, 2012)
The objective behind this work was to find out the bacteriological profile of post burn infections in wound. The study was carried out from December 2010 to February 2011 at the Burns Unit of Al –Kindy Hospital and Al-Yarmook Hospital in Baghdad. Sixty burn patients have been investigated for bacterial profile of burn wound infections. Specimens were collected in the form of wound swabs. The organisms were isolated and identified by standard microbiological methods. Antimicrobial susceptibility test has been done by ATB-PSE5 kit(BioMereiux). Pseudomonas aeruginosa 35(58.3 %) was found to be the most common isolate followed by Klebsiella pneumonae 10(16.6%), Staphylococcus aureus 7(10%). ,E.coli 3(5%), Proteus merabilis 1(1.6 %), others 2(3.3 %).and sterile cultures 2(3.3 %). Antibiotic susceptibility pattren for Pseudomonas aeruginosa isolates have shown high susptibility for Amikacin 30(85.0%), Pipracillin-Tazobactam 27(77.2%) Piperacillin 25(71.4%), Ciprofloxaqcin 25(71.4%) and Colistin 24(68.5%) and low susceptibility for Tobramycin 20(57.2%) Gentamycin 18(51.0%). Psudomonas was found to be resistant to most of the therapeutic agent.